Computer security and ethics awareness among IIUM students: an empirical study - Aliyu, Mansur; Abdallah, Nahel A. O.; Lasisi, Nojeem A.; Diyar, Dahir; Zeki, Ahmed M. (2010)
People's perception and attitude towards computer ethics and information security significantly affect the way they use information technology. This is especially the case among university students who are generally regarded as major violators of computer ethics and computer security. This paper follows previous work on computer security and ethics. The paper intend to examine the level of ethical and security awareness among IT and education students. The findings of this study reveals that there are satisfactory levels of awareness among the students surveyed with slightly higher level of awareness among IT students, most likely due to security and ethics courses they offered. Also, the findings indicate that gender-wise male students reported higher level of computer security and ethics violations than their female counterparts. The paper concludes that female students are more conscious of security and ethics while using computer (e.g. Internet) than the male students. Furthermore, IT students were found to be more aware of internet security & ethics, but largely ignore this knowledge and are more engaged in unethical activities and illegal internet practices when compared with Education students.